Dancing the two step: a phenomenological qualitative study on stroke survivors' experiences using an augmented reality system - Gisetti, Alexandra, author; Sample, Pat L., advisor; Malcolm, Matt, committee member; Pasricha, Sudeep, committee member (Colorado State University. Libraries, 2015)
Introduction: Having a stroke can be a very debilitating experience causing hemiparesis or hemiplegia. Often, when individuals are discharged home, therapeutic support decreases. This provides rehabilitation specialists with an opportunity to create an at-home, remotely-monitored therapeutic tool. Augmented reality (AR) provides a medium to meet this opportunity. The purpose of this study is to understand stroke survivors’ overall experience using AR technology as a remotely-monitored, home-based therapy program, so that rehabilitation professionals can gain a clearer view of its impact and impression on survivors’ day-to-day lives. Methods: This study incorporated a phenomenological qualitative approach, where two participants were trained on an AR system called Gator Games, and were interviewed three times over a month’s time to ascertain their lived experiences using such a system. The interviews were transcribed, coded and analyzed. Results: The following themes were identified: (1) No time to be impaired, (2) Perseverance, (3) Hope: Still trying new therapies in hopes of getting better, and (4) Having a Primary Hobby: A way to see me improve and get better. These results were confirmed through triangulating analysts, peer debrief, and member checking. Discussion: Due to technological difficulties with Gator Games, the AR system was minimally part of the participants’ daily lives, rather than being a large part of their lives. The focus of these individuals was more on their role as a family member, persevering through their symptoms and participating in a passionate hobby. Conclusion: There is a potential for this technology to be used as a remotely-monitored, at-home therapeutic tool, however, for the games to be considered more engaging, they need to be customized according to participant feedback and potentially include more mentally stimulating games versus games that focus on physical capabilities.
Keywords: experience; stroke survivors; virtual reality; stroke; augmented reality; technology